207k views
1 vote
87 POINTS PLZ HELP Aman is adding –17 + 9. He wants to write –17 as the sum of two numbers so that one of the numbers, when added to 9, will equal 0. How should Aman write –17 to complete this problem?

1 Answer

3 votes

Consider number 17. You know that

17=9+8.

Then for negative numbers you have the same rule (with respect to sign -):

-17=(-9)+(-8).

Since (-9)+9=9+(-9)=9-9=0, you have that

-17+9=(-9)+(-8)+9=(-9+9)+(-8)=0+(-8)=-8.

Answer: -17=(-9)+(-8).

User JayReardon
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.